2006
DOI: 10.1108/07363760610674310
|View full text |Cite
|
Sign up to set email alerts
|

Consumer innovativeness and perceived risk: implications for high technology product adoption

Abstract: Purpose -To investigate consumer innovativeness (CI) from a hierarchical perspective and examine the simultaneous impacts of hierarchical perspective of CI and perceived risk on new product adoption. Design/methodology/approach -An extended innovativeness and perceived risk model was developed. A structural equation model was used to test the hypotheses using empirical data from 746 respondents in a high technology product context. Findings -The results provide support for the hierarchical perspective of CI; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
226
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(265 citation statements)
references
References 103 publications
13
226
2
10
Order By: Relevance
“…Personal innovativeness is a personality trait that refers to an individual's tendency to willingly embrace change and try new things (Chau & Hui, 1998;Cotte & Wood, 2004;Roehrich, 2004;Thatcher & Perrewe, 2002), which can be further defined at either global trait level, or domain-specific level (Hirunyawipada & Paswan, 2006). Domain specific innovativeness is defined by the virtue of identifiable characteristics and actual acquisition of new information, ideas and products (Hirschman, 1980;Midgley & Dowling, 1978).…”
Section: Theories Of Personal Innovativeness and Subjective Knowledgementioning
confidence: 99%
“…Personal innovativeness is a personality trait that refers to an individual's tendency to willingly embrace change and try new things (Chau & Hui, 1998;Cotte & Wood, 2004;Roehrich, 2004;Thatcher & Perrewe, 2002), which can be further defined at either global trait level, or domain-specific level (Hirunyawipada & Paswan, 2006). Domain specific innovativeness is defined by the virtue of identifiable characteristics and actual acquisition of new information, ideas and products (Hirschman, 1980;Midgley & Dowling, 1978).…”
Section: Theories Of Personal Innovativeness and Subjective Knowledgementioning
confidence: 99%
“…Goldsmith and Hofacker (1992) argued that domainspecific innovation provides a deeper explanation of an individual's innovativeness and is highly associated with one's adoption of new products. In the literature, domain-specific innovativeness has been studied as a significant predictor of consumers' adoption of innovations (e.g., Goldsmith & Hofacker, 1992;Hirunyawipada & Paswan, 2006 Lewis, Agarwal, & Sambamurthy, 2003;Lu, Yao, & Yu, 2005). A recent study by Khare, Singh, and Khare (2010) also found that individuals' innovativeness among the Gen Y segment was a major determinant of online shopping in India.…”
Section: High-tech Involvement and Experiments Proclivitymentioning
confidence: 96%
“…The author of [2] believes that the conceptual development of innovative product models goes hand in hand with the textbook changes in the field of scienceorganization. Simultaneous impact of the hierarchical perspective of innovation and the likely risk of taking a new product to production is considered in [3]. [4] is devoted to the risk of supply of material resources and reduction of possible investments due to the reduction of the complexity of the innovation project.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%